DNA polymerase β decrement triggers death of olfactory bulb cells and impairs olfaction in a mouse model of Alzheimer's disease. Issue 1 (30th September 2016) - Misiak, Magdalena; Vergara Greeno, Rebeca; Baptiste, Beverly A.; Sykora, Peter; Liu, Dong; Cordonnier, Stephanie; Fang, Evandro F.; Croteau, Deborah L.; Mattson, Mark P.; Bohr, Vilhelm A.
Summary: Alzheimer's disease (AD) involves the progressive degeneration of neurons critical for learning and memory. In addition, patients with AD typically exhibit impaired olfaction associated with neuronal degeneration in the olfactory bulb (OB). Because DNA base excision repair (BER) is reduced in brain cells during normal aging and AD, we determined whether inefficient BER due to reduced DNA polymerase‐β (Polβ) levels renders OB neurons vulnerable to degeneration in the 3xTgAD mouse model of AD. We interrogated OB histopathology and olfactory function in wild‐type and 3xTgAD mice with normal or reduced Polβ levels. Compared to wild‐type control mice, Polβ heterozygous (Polβ +/− ), and 3xTgAD mice, 3xTgAD/Polβ +/− mice exhibited impaired performance in a buried food test of olfaction. Polβ deficiency did not affect the proliferation of OB neural progenitor cells in the subventricular zone. However, numbers of newly generated neurons were reduced by approximately 25% in Polβ +/− and 3xTgAD mice, and by over 60% in the 3xTgAD/Polβ +/− mice compared to wild‐type control mice. Analyses of DNA damage and apoptosis revealed significantly greater degeneration of OB neurons in 3xTgAD/Polβ +/− mice compared to 3xTgAD mice. Levels of amyloid β‐peptide (Aβ) accumulation in the OB were similar in 3xTgAD and 3xTgAD/Polβ +/− mice, and cultured Polβ‐deficient neurons exhibited increased vulnerability to Aβ‐induced death. Olfactory deficit is an early sign in human AD, but the mechanism is not yet understood. Our findings in a new AD mouse model demonstrate that diminution of BER can endanger OB neurons, and suggest a mechanism underlying early olfactory impairment in AD.